HUBUNGAN KOMUNIKASI INTERPERSONAL DENGAN PERILAKU BULLYING PADA SISWA - Zita Fakhirani Idzni (PUSKAPAD, 2025)
This study aims to determine the relationship between interpersonal communication and bullying behavior in class IX students of Karya Jaya Private Middle School, Tanjung Morawa. The hypothesis proposed is that there is a positive and significant relationship between interpersonal communication and bullying behavior in class IX students at Karya Jaya Private Middle School, Tanjung Morawa. The research method used is a quantitative descriptive approach with the type of research used is correlational descriptive research. The determination of the sample of this study is a population study of 86. The sample in this study was 40 people to obtain the necessary data, so in this study the researcher used data collection tools in the form of questionnaires and documentation. Furthermore, the results of the study at Karya Jaya Tanjung Morawa Private Middle School used product moment correlation calculations. The two variables were bullying behavior (X) and interpersonal communication (Y). The level of student bullying behavior was 68.12% in the high category, the level of interpersonal communication was 63.12% in the high category, the level of interpersonal communication relationship with bullying behavior was r_count 0.269> r_table 0.331. This shows that there is a relationship between interpersonal communication and bullying behavior in students. Based on the discussion and data analysis, it can be concluded that the hypothesis stating